World Health Organization Classification of Odontogenic Tumors and Imaging Approach of Jaw Lesions - Siozopoulou, Vasiliki; Vanhoenacker, Filip M. (Seminars in Musculoskeletal Radiology, 2020)
Tumors of the jaws represent a heterogeneous group of lesions that are classified histologically in the World Health Organization Classification of Odontogenic Tumors (2017). This article provides an update of the current nomenclature. The main role of imaging is to describe the precise location and extent of these lesions. Although characterization of imaging is often difficult due to overlapping characteristics, imaging is helpful to define which lesions should be referred for histologic examination and subsequent treatment planning. Location and density are the cardinal criteria for potential characterization on imaging. Radiologically, lesions may be radiolucent, radiopaque, or of mixed density. Additional criteria include lesion demarcation, morphology, cortical breakthrough, periosteal reaction, and adjacent soft tissue changes. Final lesion characterization is only definitive after interdisciplinary discussion and radiopathologic correlation. Correct diagnosis is obtained by a combination of the patient's age, lesion location, and clinical and radiologic presentation. It is important that all physicians use a uniform nomenclature.
Keywords: jaws; histopathology; radiography; cone-beam computed tomography